Comparison of efficacy of oral ivermectin and topical permethrin 5% in the treatment of scabies - Maimona Ilyas; Atif Shahzad; Saadiya Siddiqui; Mohsina Awais; Maryam Qayyum; Ali Azafar, Nadia (Journal of Pakistan Association of Dermatologists, 2023)
Background Scabies an ectoparasitic infection caused in humans by the sarcoptes scabiei var.hominis.Ivermectin, an antiparasitic agent effective against a variety of ectoparasites and endoparasites . Permethrin an insecticide, applied topically kills the mite and its eggs, although patients may still experience some itching for several weeks. Objective: To compare the efficacy of oral ivermectin and topical permethrin 5% in treatment of scabies. Methadology : It was a randomized controlled trial conducted at Dermatology Department; Sir Gangaram Hospital Lahore / Fatima Jinnah Medical University Lahore. Sixty enrolled patients after informed consent were divided in 2 groups i.e. group-A and group-B. In group-A ,cases were treated with Tab ivermectin orally in dose of 200mcg/kg at day 0 and in group-B all cases were treated with topical permethrin 5% at day 0.The lesions were examined and compared with baseline clinical grading and itch grading scores .The cured patients were provided antihistamines for further 1 week if itching is moderate to severe.Efficacy was determined after one week of tretment. Results: Mean age in patients who recieved Permethrin 5 % was 41.67 ± 10.35 years and those received Ivermectine mean age was 39.67 ± 12.38 years. In Permethrin 5% group, 22(73.3%) cases showed efficacy and Ivermectine group 8(26.7%) cases showed efficacy (p-value < 0.05). Permethrin (5%) remained more efficacious. Conclusion: Scabies can be treated with permethrin 5% to achieve higher cure, by doing so we can improve patient’s quality of life. Keywords: Scabies, oral ivermectin, permethrin, efficacy, safety, side effects